Genome sequences of triacylglycerol metabolism in Rhodococcus as a platform for comparative genomics - Villalba, María S. (2013)
Bacteria belonging to the Rhodococcus genus are usu-ally able to synthesize and accumulate variable amounts of triacylglycerols (TAG) from diverse car-bon sources. Although some significant advances in the basic knowledge on TAG metabolism in rhodococci have been made, the fundamental under-standing of this process and its regulation remains to be clarified. The abundantly available genomic infor-mation for several rhodococcal species provides the possibility for comparative genome analysis on the occurrence and distribution of key genes and pathways involved in TAG metabolism. Our bioinformatic analyses of available databases from six rhodococcal strains demonstrated that genes/enzymes for reactions related to TAG biosynthesis and degradation, and fatty acid β-oxidation are surprisingly abundant in rhodococcal genomes. Several genes/enzymes of glyc-erolipids and fatty acid metabolism are highly repre-sented in the analyzed genomes. A number of previ-ously undescribed, new putative genes for glycerolipid metabolism in rhodococci have been identified and the size of each family has been estimated.